Metabolism and disposition of oseltamivir (OS) in rats, determined by immunohistochemistry with monospecific antibody for OS or its active metabolite oseltamivir carboxylate (OC): A possibility of transporters dividing the drugs’ excretion into the bile and kidney - Kunio Fujiwara; Yutaro Yamamoto; Tetsuya Saita; Senya Matsufuji (Pharmacology Research & Perspectives, 2020)
Abstract Among any drugs, no comparative pharmacological study on how prodrug and its active metabolite behave in animal bodies is available. Immunohistochemistry (IHCs) using newly prepared two monoclonal antibodies, AOS‐96 and AOC‐160, monospecific for oseltamivir (OS) and its metabolite oseltamivir carboxylate (OC) were developed, simultaneously detecting the uptake or excretion of OS and OC in the intestine, liver, and kidney of rats to which OS was orally administered. In the intestine, IHC for OS revealed OS highly distributed to the absorptive epithelia with heavily stained cytoplasmic small granules (CSGs). IHC for OC showed that OC also distributed highly in the epithelia, but without CSGs, suggesting that OS was partly converted to OC in the cells. In the liver, OS distributed in the hepatocytes and on their bile capillaries, as well as on the lumina from the bile capillaries to the interlobular bile ducts. OC distributed in the whole cell of the hepatocytes, but without CSGs nor on any lumina through the interlobular bile ducts. In the kidney, a few levels of OS distributed in the cytoplasm of almost all the renal tubule cells, but they contained numerous CSGs. In contrast, OC distributed highly in the proximal tubules, but very slightly in the lower renal tubules of the nephrons. Thus, it was concluded that the two drugs behave in completely different ways in rat bodies. This paper also discusses a possibility of the correlation of OS or OC levels in tissue cells with their known transporters.